ASSESSING POSTPARTUM BLUES: A PRELIMINARY APPROACH THROUGH A PILOT STUDY - Ika Novita Sari; bin Sansuwito, Tukimin (Sahabat Publikasi Kuu, 2025)
Background: Postpartum blues is a common mood disorder affecting postpartum mothers, with potential impacts on maternal mental health and infant development. Early identification using valid and reliable instruments is essential for appropriate management. Objective: This study aimed to examine the validity and reliability of the Postpartum Blues Scale and identify the prevalence and risk factors of postpartum blues among postpartum mothers in the working area of the Health Center in Batam. Methods: A pilot study with a cross-sectional design was conducted on 30 postpartum mothers from January to March 2024. Data were collected using the Postpartum Blues Scale, comprising 32 items across six dimensions, scored on a 0-3 scale. The instrument was evaluated for validity and reliability, and associations between variables were analyzed using appropriate statistical tests. Results: The Postpartum Blues Scale demonstrated good psychometric properties (Cronbach's alpha = 0.89). The overall prevalence of postpartum blues was 70%, with mild (40%), moderate (20%), and severe (10%) symptoms. Significant risk factors included lower educational level (p = 0.032), primiparity (p = 0.041), a cesarean delivery (p = 0.045), and inadequate social support (r = 0.68, p = 0.001). The most prevalent symptoms were excessive fatigue (83.3%), anxiety about the baby's health (80%), and mood swings (76.7%). Conclusion: The Postpartum Blues Scale is a valid and reliable instrument for assessing postpartum blues. The high prevalence and identified risk factors highlight the need for routine screening and targeted interventions in primary healthcare settings.